Dacie and Lewis practical haematology - Bain, Barbara J.; Dacie, John V. [ (John Vivian)] , Sir; Lewis, S. M. [ (Shirley Mitchell)] (Elsevier Churchill Livingstone, 2012)
Covers the techniques used in the investigation of patients with blood disorders. This title discusses the principles of various tests, possible causes of error, the rationale for choosing one method over another and the interpretation, significance and clinical relevance of these findings